(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Fazan V. V. Elucidative to activity of Large monastery in Ukraine (XVII– XVIIІ in.) Pre-conditions are considered and described which was instrumental in becoming of elucidative activity Large monasteries in Ukraini. Positive influence of Large monasteries is analysed on formation of society.